Heat transfer effects on carbon nanotubes along a moving flat plate subjected to uniform heat flux - Ferdows, M.; Shamshuddin, Md.; Reza, Motahar; Quadir, Raushan Ara (Zielona Góra: Uniwersytet Zielonogórski)
In the present paper, a theoretical analysis is made to investigate fluid flow and heat energy transformation features of single and multi-walled water functionalized carbon nanotubes (CNTs) with uniform heat inconstancy boundary conditions onward a flat plate. The liquid motion and momentum transfer of carbon nanotubes (CNTs) have been analyzed using a homogeneous flow model.
Keywords: SWCNTs; MWCNTs; heat transfer; bvp4c; similarity